Moracin N as a Potential Anti-Obesity Agent via Modulation of Steroid Hormone Metabolism: A Network Pharmacology and Docking Study - Wimzy Rizqy Prabhata; Galuh Yogi Pratama; Shilvia Anggun Tiara Kaldella (Jurnal FARMASIMED (JFM), 2026)
Background: Obesity is a global health problem with a rapidly increasing prevalence, while available pharmacological therapies remain limited and are often associated with adverse effects. Although bioactive compounds from Morus alba have been widely investigated, the anti-obesity potential of Moracin N remains largely unexplored, creating a knowledge gap regarding its molecular mechanisms and protein targets. Objectives: This study aimed to evaluate the anti-obesity potential of Moracin N using network pharmacology and molecular docking approaches. Methods: Potential targets of Moracin N were predicted using SwissTargetPrediction, TargetNet, and Super-PRED, while obesity-related targets were obtained from OMIM and GeneCards. Network analysis was performed using STRING and Cytoscape, followed by enrichment analysis (gene ontology biological process and KEGG). Docking studies were conducted on HSD17B13, HPGD, and STS using PLANTS and visualized with PyMOL. Results: The analysis identified 62 overlapping targets (4.8%), mainly involved in steroid hormone biosynthesis, metabolism, and inflammatory regulation. Key proteins, including CYP19A1, CYP17A1, CYP11B2, pro-inflammatory cytokines (IL1B, TNF, IL6), and metabolic enzymes (HSD17B13, STS, HPGD), occupied central positions in the protein–protein interaction network. Docking results demonstrated strong binding affinity of Moracin N, particularly toward STS, with amino acid residue interaction patterns comparable to those in reference ligands. Conclusion: Overall, Moracin N shows potential as a multi-target anti-obesity agent, primarily through modulation of steroid hormone metabolism. However, these findings remain predictive and require further experimental validation.